2023
DOI: 10.3390/pathogens12020289
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Major QTL-Controlling Resistance to the Subtropical Race 4 of Fusarium oxysporum f. sp. cubense in Musa acuminata ssp. malaccensis

Abstract: Vascular wilt caused by the ascomycete fungal pathogen Fusarium oxysporum f. sp. cubense (Foc) is a major constraint of banana production around the world. The virulent race, namely Tropical Race 4, can infect all Cavendish-type banana plants and is now widespread across the globe, causing devastating losses to global banana production. In this study, we characterized Foc Subtropical Race 4 (STR4) resistance in a wild banana relative which, through estimated genome size and ancestry analysis, was confirmed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 74 publications
0
14
1
Order By: Relevance
“…Some contracted gene families in the ‘Baxijiao’ genome were involved in the biological processes associated with response to external biotic and abiotic factors. Accumulating evidence indicates that banana cultivars have generally reduced resistance to pathogens and environmental stresses than their wild ancestors [ 43 , 44 ]. These contracted gene families will provide candidates for further investigations on the genetic basis of the reducing resistance in banana cultivars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some contracted gene families in the ‘Baxijiao’ genome were involved in the biological processes associated with response to external biotic and abiotic factors. Accumulating evidence indicates that banana cultivars have generally reduced resistance to pathogens and environmental stresses than their wild ancestors [ 43 , 44 ]. These contracted gene families will provide candidates for further investigations on the genetic basis of the reducing resistance in banana cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Here we found that considerably fewer resistance genes were identified in ‘Baxijiao’ than in wild banana M. acuminata . Recently, Chen et al [ 44 ] have identified a major quantitative trait loci (QTL)controlling resistance to the subtropical race 4 (STR4, affecting Cavendish bananas in the subtropics) of Foc in M. acuminata ssp. malaccensis .…”
Section: Discussionmentioning
confidence: 99%
“…Although one critical recombinant (852-7) did not produce any symptoms in the TR4 screening, the phenotypic data were generally concordant with the genetic interval defined for both STR4-and TR4resistant loci. Within this interval, there was a cluster of receptor-like kinases (LRR XII subfamily) and receptor-like proteins (LRR RLP subfamily) positioned in an interspersed arrangement [57]. They, respectively, belong to the LRR XII and LRR RLP subfamilies of pattern recognition receptors [72,77].…”
Section: Discussionmentioning
confidence: 99%
“…malaccensis parents were used in this study. The progenies of the R (resistant) parents 'Ma850', 'Ma851', and 'Ma852' segregated for Foc-STR4 and Foc-TR4 resistance [57,58], whereas the S (susceptible) parents 'Ma845', 'Ma846', and 'Ma848' were uniformly susceptible to Foc-STR4 (Figure 1A). Three close-pollinated F 2 populations, collectively called Population 1 and consisting of 435 individuals, were developed for mapping.…”
Section: Musa Acuminata Ssp Malaccensis Populationsmentioning
confidence: 99%
See 1 more Smart Citation